Pharmacists knowledge, perception and practice regarding medication disposal - Satish Jankie; Arlene Villarroel Stuart; Naveeta Barsatee; Vicky Dookhan; Kadita Sookdeo; Sasha Hernandez; Cheyenne Mohammed (Elsevier, 2022)
Background: Medications that are improperly disposed contribute to environmental contamination with proven negative impacts on biological ecosystems. The role of the pharmacist in providing medication disposal advice is paramount to reducing this effect. Objective: To investigate pharmacists' knowledge, perception and practices regarding medication disposal in Trinidad. Methods: A cross-sectional study was conducted electronically over 4 months amongst public and private sector pharmacists using a self-administered questionnaire. The questionnaire comprised 32 questions and four sections - demographics, knowledge, perception and practice regarding medication disposal. Ethical approval was obtained from the Ethics Committee, the University of the West Indies, the four Regional Health Authorities in Trinidad, and the Ministry of Health, Government of the Republic of Trinidad and Tobago. Data were analysed using IBM SPSS Statistics Version 24. Chi-squared tests sought to detect significant associations between demographics and responses. Results: Of 400 pharmacists, (response rate 52.0%) most were female (63.0%), had <5 years experience (47.1%), and worked in a community pharmacy (68.0%). Most (79.3%) believed that improperly disposed medications can negatively affect the environment but only 45.2% thought that improperly disposed antibiotics could lead to antimicrobial resistance. Most returned expired drugs to the pharmaceutical distributor (80.8%), or disposed of through the Drug Inspectorate (63.9%), but 32.3% still disposed of expired medicines in the workplace garbage, with community pharmacies being more likely to carry out this practice (p = 0.011). Most pharmacists (36.5%) do not counsel patients on medication disposal and 64.4% would not recommend flushing expired drugs down the toilet. Only 20.7% would recommend flushing narcotics, which is considered the best practice to prevent accidental poisoning. Conclusions: Continuing education for pharmacists is needed to increase awareness of the best practices of medication disposal, along with an awareness campaign on medication disposal.